2020
DOI: 10.1101/2020.04.15.039842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prostacyclin Promotes Degenerative Pathology in a Model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is the most common cause of dementia in aged populations. A substantial amount of data demonstrates that chronic neuroinflammation can accelerate neurodegenerative pathologies, while epidemiological and experimental evidence suggests that the use of anti-inflammatory agents may be neuroprotective. In AD, chronic neuroinflammation results in the upregulation of cyclooxygenase and increased production of prostaglandin H2, a precursor for m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…Previous studies in our lab described exacerbated pathology and harmful cerebral vascular effects of prostacyclin overexpression in the APdE9 animal model of AD [9]. We found that upregulated prostacyclin expression significantly worsened cognitive abnormalities, accelerated amyloid pathology, and damaged the neurovasculature PGI2 overexpression selectively increased soluble amyloidβ 42 production, total amyloid accumulation, and burden.…”
Section: Introductionsupporting
confidence: 46%
“…Previous studies in our lab described exacerbated pathology and harmful cerebral vascular effects of prostacyclin overexpression in the APdE9 animal model of AD [9]. We found that upregulated prostacyclin expression significantly worsened cognitive abnormalities, accelerated amyloid pathology, and damaged the neurovasculature PGI2 overexpression selectively increased soluble amyloidβ 42 production, total amyloid accumulation, and burden.…”
Section: Introductionsupporting
confidence: 46%
“…The content of this manuscript has been used in the dissertation of the first author, Dr. TW. This manuscript has also appeared online as a preprint in bioRxiv (Womack et al, 2020).…”
Section: Author Contributionsmentioning
confidence: 99%